Knowledge, Attitudes and Compliance with Infection Prevention and Control Practices Among Nursing and Medical Laboratory Science Students in Koforidua. - Awekeya, H. (University of Ghana, 2019)
Introduction: There is a huge burden of Health care associated infections (HAIs) globally; in 2002, there was an estimated 99,000 deaths due to HAIs in the United States and majority of these are attributed to poor compliance of health care workers including health sciences students to Infection Prevention and Control protocols (IPC). Health science students by virtue of their training are at risks of spreading or contracting HAIs due to lack of knowledge and in-experience. Method: An analytical cross-sectional study was undertaken in two tertiary institutions in Koforidua, Eastern Region. A total of 252 nursing students from the Nursing and Midwifery Training College, Koforidua and 122 medical laboratory science (MLS) were assessed on their knowledge, attitudes and compliance to IPC measures. Data was collected using a structured questionnaire to assess students’ knowledge, attitudes and compliance on elements of IPC. Scores were calculated in percentages and differences in scores among both categories made. Associations between knowledge, attitudes, and compliance and the independent variables was also determined through logistic linear regression. A p value <0.05 was considered as significant. Results: A total 354 out of 374 students had complete data with a response rate of 94.7%. More than half (232/354) were nursing students and 34.5% (122/354) being medical laboratory science (MLS) students. On Average knowledge scores were poor, 44.7%, attitude scores were satisfactory, 80.9% and compliance rates were satisfactory, 88.8% respectively. Third year students on average performed better with knowledge scores of 49.2% compared to second and first year students with 43.2% and 40.4% respectively. Again, third year students had higher attitude scores, 82.3% compared to second and first year students with scores of 80.4% and 78.0% respectively. These scores were statistically significant, p value<0.05. Female students were also reported to be significantly more compliant (89.6%) with IPC practices than their male counterparts (86.3%), p value<0.05. There was however no significant difference in knowledge scores of MLS or nursing students. Conclusion: Both student groups had poor knowledge in IPC but reported positive attitudes and satisfactory compliance rates. Effective and continuous teaching and learning of IPC throughout the years of study both in the classroom and during clinical rotation will help improve knowledge as well attitudes and compliance of students. Keywords: Knowledge, Attitude, Compliance, Infection Prevention and Control, Healthcare Trainees, Koforidua.
MPH.
Keywords: Healthcare Trainees; Koforidua; Infection Prevention and Control; Attitude